2012
DOI: 10.1097/brs.0b013e31823b0440
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Granulocyte Colony-Stimulating Factor Treatment Promotes Functional Recovery in Rats With Severe Contusive Spinal Cord Injury

Abstract: Delayed G-CSF treatment at the subacute stage of severe contusive SCI promoted spinal cord preservation and improved functional outcomes. The mechanism of G-CSF's protection may be related in part to attenuating the infiltration of microglia and macrophages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…However, comparison of PI with FJ orientation at the upper lumbar spine did not reveal any significant differences. This is similar to a recent study by Toy et al [37], who investigated 120 cadaver specimen and concluded that the highest quarter of pelvic lordosis is associated with FJ arthritis at L5/S1. According to Toy et al [37], pelvic lordosis describes the angle between the pelvic radius line and a line tangent to the upper S1 endplate that intersected at the posterior superior corner of S1.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, comparison of PI with FJ orientation at the upper lumbar spine did not reveal any significant differences. This is similar to a recent study by Toy et al [37], who investigated 120 cadaver specimen and concluded that the highest quarter of pelvic lordosis is associated with FJ arthritis at L5/S1. According to Toy et al [37], pelvic lordosis describes the angle between the pelvic radius line and a line tangent to the upper S1 endplate that intersected at the posterior superior corner of S1.…”
Section: Discussionsupporting
confidence: 92%
“…(5) Facet joint (FJ) arthritis may arise from several misbalanced forces, such as increased LL, which leads to higher contact forces on the FJs, compression, rotation, and shear as well as more sagittal orientation of the lower lumbar spine, which may lead to spondylolysis and spondylolisthesis [31-36]. However, this may be prevented by compensatory mechanisms of the pelvis and a previous osteologic study [37] has linked increased pelvic lordosis to FJ arthritis at L5/S1. Other previous studies [38,39] have also found an association between the pelvic geometry and lumbar degenerative processes.…”
Section: Introductionmentioning
confidence: 99%
“…That is, while GCSF is upregulated in tSCI, it is downregulated in cSCI with time-to-time changes also in contrary motion with the exception of day 56. As purified GCSF administration alone and in combination with adipose- and bone-marrow-derived stem and neural stem cells has been shown to be highly beneficial in rodent and human tSCI—including increased tissue preservation, reduced apoptosis and scarring, and improved BBB, BMS and A [46,47,48,49,50,51,52,53,54,55,56]—such a paradigm may prove to be even more effective in the all stages of cSCI where a deficiency in GCSF is seen.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have already evidenced the beneficial effects of G-CSF in experimental models of SCI [80,81], which seem to be mainly associated with the prevention of excitotoxicity and apoptotic neuronal death, through several possible mechanisms [82]. G-CSF upregulates chaperone proteins, such as nucleophosmin-1 in motoneurons after spinal cord hemisection [83], reduces myeloperoxidase activity and lipid peroxidation [84] and increases glial cell line-derived neurotrophic factor and vascular endothelial growth factor A expression in glial cells after spinal cord ischemia [85].…”
Section: Granulocyte Colony-stimulating Factor: Its Implication In Exmentioning
confidence: 99%